2014
DOI: 10.3892/or.2014.3657
|View full text |Cite|
|
Sign up to set email alerts
|

miR-218 suppresses tumor growth and enhances the chemosensitivity of esophageal squamous cell carcinoma to cisplatin

Abstract: Abstract.A growing body of evidence suggests that microRNA-218 (miR-218) acts as a tumor suppressor and is involved in tumor progression, development and metastasis and confers sensitivity to certain chemotherapeutic drugs in several types of cancer. However, our knowledge concerning the exact roles played by miR-218 in esophageal squamous cell carcinoma (ESCC) and the underlying molecular mechanisms remain relatively unclear. Thus, the aims of this study were to detect the expression of miR-218 in human ESCC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 43 publications
0
22
0
Order By: Relevance
“…These miRNAs are associated with different etiologies, metastasis, the propensity for recurrence and prognosis as a molecular signature in human types of cancer (10,11). Recent findings have showed that miRNAs are important in the drug resistance of different tumors (12)(13)(14). Given the close relationship between miRNAs and the biological progression of various types of cancer, miRNAs are considered potential novel targets for the therapy of various types of cancer (15).…”
Section: Introductionmentioning
confidence: 99%
“…These miRNAs are associated with different etiologies, metastasis, the propensity for recurrence and prognosis as a molecular signature in human types of cancer (10,11). Recent findings have showed that miRNAs are important in the drug resistance of different tumors (12)(13)(14). Given the close relationship between miRNAs and the biological progression of various types of cancer, miRNAs are considered potential novel targets for the therapy of various types of cancer (15).…”
Section: Introductionmentioning
confidence: 99%
“…Reports also showed that miR-218 might act as tumor suppressor in a variety of human cancer types [12,15,16]. In addition, increased expression of miR-218 can enhance the chemosensitivity to cisplatin [17,18]. These results indicated that miR-218 may have a correlation with the resistance during lung cancer chemotherapy.…”
Section: Introductionmentioning
confidence: 71%
“…Extensive studies have indicated that tumor-targeting therapies using miRNAs are becoming a novel diagnostic and therapeutic tool [21]. A number of studies have indicated that miR-218 is involved in the chemosensitivity to cisplatin process in certain tumors and that upregulation of miR-218 may partially enhance cell death [17,18]. Consistently, in our present study, miR-218 was noteworthy downregulated in the A549/DDP cisplatin-resistant lung cancer cell lines compared with that in non-resistant A549 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Aberrant expression of miRNAs is associated with tumor development through regulation of their respective target genes. For example, miR-218 was reported to suppress the growth of esophageal squamous cell carcinoma by regulating the PI3K/AKT/mTOR pathway (14). miR-17 and miR-106b are frequently downregulated in the serum of gastric cancer patients, which may therefore be utilized as tumor markers for the early diagnosis of gastric cancer (15).…”
Section: Introductionmentioning
confidence: 99%